Standards for Management of Islamic Religious Education in Indonesia - Lukman Surya; Tetra Jumif Januarius (International Research of Economic and Management Education, 2021)
Islamic Religious Education is the main subject in accordance with the 2013 curriculum, in line with this for the sake of implementing the teaching and learning process in order to fulfill the indicators listed in the lesson plans and syllabus. Learning management is the teacher's task, starting from making lesson plans, learning processes, and evaluating learning. Teachers are required to implement the principles of learning management, namely Planning, Organizing, Movement, and Controlling Supervision. Then the Islamic Religious Education Teachers at SMA have implemented the above principles and even then, what is done by Islamic Religious Education teachers at SMAN 2 and SMAN 7 Bandar Lampung carry out the learning management process well, starting with planning as outlined in the manufacture of complete learning tools, then starting the process learning begins with opening activities, then the core activity is the process of providing material and ends with closing. Furthermore, the learning evaluation process is carried out using various techniques, both in writing and orally. It can be concluded that if the implementation of learning management standards in the world of Indonesian education should have been carried out in accordance with what has been carried out by Islamic Religious Education teachers at SMAN 2 and SMAN 7 Bandar Lampung, the stages in the learning process and are considered very good and have been completed. in accordance with the principles of learning management in Indonesia.